Teaching literature searching in the context of the World Wide Web. - Brandt, K. A. (American Medical Informatics Association, 1995)
As part of the required curriculum for medical students, we devised a literature-searching practicum that has been used for two years. In both years, we stressed going beyond the skills needed for using a particular searching program, towards a more conceptual approach to information searching. In the first year, the practicum was taught in a traditional lecture/hands-on format. In the second year, the lecture was replaced by a World Wide Web-based tutorial (http:@www.welch.jhu.edu/Education/tutorials/pra cticum.html). To our knowledge, this is the first Web-based resource intended to teach students about appropriate use of search technology. Comparison of student evaluations showed no difference in attitude toward the two versions of the practicum, and observation of student performance suggested similar levels of proficiency. We conclude that placing these educational materials on the Web (1) makes us practice what we preach; (2) is as effective as traditional teaching methods; and (3) gives students a resource for reinforcement learning.